The influence of poultry manure on the yield and crop structure of spring rapeseed - E. N. Volodina; V. I. Titova; D. A. Kirillova (Аграрная наука Евро-Северо-Востока, 2024)
The research was carried out to identify the optimal dose of bedding bulk poultry manure on the influence of the crop structure and the yield of spring rape seeds of Lunedi variety. The work was carried out in 2022-2023 in the forest-steppe zone of the Nizhny Novgorod region. Poultry manure loose (GOST 31461-2012) was applied in doses of 4, 6 and 8 t/ha (control - without fertilizers). The experiment was conducted on light gray forest loamy soil with low humus content, neutral reaction and mobile forms of phosphorus and potassium. Statistically proven changes in the structure of rape yield were noticed on the manured variants: the increase in length of the fruit (pod) was 0.40–0.67 cm, in pod weight – 0.04–0.12 g, the number of pods per plant increased by 1.4–2.1 times, the number of seeds in a pod increased by 2.5–4.6 seeds, seed productivity of a single plant increased by 1.9–3.0 times, the weight of 1000 seeds exceeded by 0.66–0.94 g. The application of poultry manure on all variants revealed a reliable increase in the yield of above-ground phytomass and seeds, the increase in rape biomass was 6.03–8.70 t/ha (LSD05 = 1.30), seeds – 0.94–1.26 t/ha (LSD05 = 0.46). The maximum increase in the biomass of rapeseed and seeds (6.03 and 0.94 t/ha) was established in the variant with a manure dose of 4 t/ha, since with an increase in the manure dose (6 and 8 t/ha) in excess of the minimum increase by 1.42–2.67 t/ha of plant biomass and 0.22–0.32 t/ha of seeds. The obtained results suggest that the optimum dose of poultry manure application to spring rapeseed on light grey forest soil (Alfisol) is 4 t/ha.